Control, Computation and Information Systems First International Conference on Logic, Information, Control and Computation, ICLICC 2011, Gandhigram, India, February 25-27, 2011. Proceedings - Balasubramaniam, P.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the International Conference on Logic, Information, Control and Computation, ICLICC 2011, held in Gandhigram, India, in February 2011. The 52 revised full papers presented were carefully reviewed and selected from 278 submissions. The papers are organized in topical sections on control theory and its real time applications, computational mathematics and its application to various fields, and information sciences focusing on image processing and neural networks.
Keywords: Computer science; Computer software; Information systems; Artificial intelligence; Computer vision; Optical pattern recognition; Computer Science; Algorithm Analysis and Problem Complexity; Computation by Abstract Devices; Artificial Intelligence (incl. Robotics).; Pattern Recognition; Image Processing and Computer Vision; Information Systems Applications (incl.Internet).